Live to see the day : coming of age in American poverty - Goyal, Nikhil (Metropolitan Books, Henry Holt and Company, 2023)
"Kensington, Philadelphia, is distinguished only by its poverty. It is home to Ryan, Giancarlos, and Emmanuel, three Puerto Rican children who live among the most marginalized children and families in the United States. This is their coming-of-age story. It is also the story of families beset by violence--the violence of homelessness, hunger, incarceration, stray bullets, sexual and physical assault, the hypermasculine logic of the streets, and the drug trade. In Kensington, eighteenth birthdays are not rites of passage but statistical miracles. One mistake puts Ryan in the juvenile justice pipeline. Giancarlos can't afford to stop dealing and get off the corner. For Emmanuel, his queerness means his mother's rejection and sleeping in shelters. The three are school dropouts, but they are on a quest to defy their fate and their neighborhood and get high school diplomas. In a triumph of empathy, Nikhil Goyal follows Ryan, Giancarlos, and Emmanuel on their quest, plunging deep into their lives as they strive to resist their designated place in the social hierarchy. In the process, Live to See the Day confronts a new age of American poverty, after the end of "welfare as we know it," after "zero tolerance" in schools criminalized a generation of students, after the odds of making it out are ever slighter"--